Recent advances in the role of polysaccharides in liver diseases: a review - Wang, Junfeng; Wang, Hanxiang; Yang, Xiawen; Wang, Kaiping; Zhang, Yu (Frontiers in Pharmacology, 2025)
Liver diseases are a serious health problem worldwide, especially with a sustained increase in the burden of it every year. However, drugs commonly used in patients have limited efficacy and serious adverse reactions associated with long-term use. Therefore, it is urgent to find effective and safe alternatives. Polysaccharides are currently considered promising alternatives to traditional drugs because of their extensive activity and low toxicity. This review investigated the studies on hepatoprotective polysaccharides over the past 6 years, detailing their hepatoprotective effects, potential mechanisms, and drug carrier applications. These findings suggest that polysaccharides have prominent preventive and therapeutic effects on various liver diseases such as drug-induced liver injury, alcoholic liver disease, hepatitis B, non-alcoholic fatty liver disease, liver fibrosis, and hepatocellular carcinoma. Its mechanism includes multiple aspects such as metabolic regulation, reduction of oxidative stress and inflammation, and regulation of gut microbiota. Furthermore, owing to the good physicochemical properties, polysaccharides have been applied in delivery systems for chemotherapy drugs and small molecule drugs. However, further research is essential on the bioavailability, structure-activity relationship, and more clinical evidence of polysaccharides. Continued exploration of polysaccharides will provide tremendous potential for the treatment of liver diseases.